Efektivitas Kampanye Moderasi Beragama Berbasis Whatsapp Group pada Masyarakat Desa - Utomo, Sholeh; Heriansyah, Dafis; Mauizah, Adzkiya Zayyan; Apriliani, Devi Rizki; Ruslan, Idrus (Jurnal Riset Agama, 2021)
This study aims to discuss the effectiveness of WhatsApp Group-based religious moderation campaigns in rural communities. This research departs from the phenomenon of religious moderation campaigns/symbols using WhatsApp Group (WAG) which occurred in Padang Rejo Village, Pagelaran District, Pringsewu Regency, Lampung Province. This study uses a descriptive-qualitative method through a field study approach (field research). The results and discussion of this study indicate that the WhatsApp Group (WAG)-based religious moderation campaign is fairly effective. The factors that drive this effectiveness are: first, the use of the WhatsApp application is a daily activity for citizens to communicate with one another; second, the public's lack of understanding in sorting and selecting information on social media, especially the content of religious lectures, thus requiring guidance and control from religious leaders; third, it would be very dangerous if the people of origin took or listened to lectures that smelled of radicalism and fanaticism; Fourth, the existence of religious leaders who choose content that is worthy of being listened to by the public will guarantee public understanding in the right direction in religion, namely being moderate. This study also recommends religious leaders or village heads as a solution to the campaign of religious moderation in village communities.